2016
DOI: 10.1038/srep31639
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the growth mechanism of graphene on Ge/Si(001) surfaces

Abstract: The practical difficulties to use graphene in microelectronics and optoelectronics is that the available methods to grow graphene are not easily integrated in the mainstream technologies. A growth method that could overcome at least some of these problems is chemical vapour deposition (CVD) of graphene directly on semiconducting (Si or Ge) substrates. Here we report on the comparison of the CVD and molecular beam epitaxy (MBE) growth of graphene on the technologically relevant Ge(001)/Si(001) substrate from et… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 41 publications
6
59
4
2
Order By: Relevance
“…Dabrowski et al presented a detailed understanding of direct CVD growth mechanism of graphene on Ge (001)/Si (001) substrates 132. Prior to the graphene growth, 2 µm thick Ge (001) layers were grown on 200 mm Si (001) wafers by CVD 130, 133.…”
Section: Catalyst‐free Direct Cvd Growth Of Graphene On Technologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Dabrowski et al presented a detailed understanding of direct CVD growth mechanism of graphene on Ge (001)/Si (001) substrates 132. Prior to the graphene growth, 2 µm thick Ge (001) layers were grown on 200 mm Si (001) wafers by CVD 130, 133.…”
Section: Catalyst‐free Direct Cvd Growth Of Graphene On Technologicalmentioning
confidence: 99%
“…The typical heights of the facets and R a values were found to be 2–5 nm and 0.7–1.1 nm, respectively [from AFM image (Figure 17g)]. Generally, the majority of crystallites are oriented either parallel or perpendicular to the (110) axis in the CVD graphene on Ge (001), where the carbon hexagons have sides either parallel or perpendicular to the surface dimer rows (Figure 17h) 121, 123, 131, 132. It could be possible that the small graphene grains with the same orientation could coalesce into larger strained grains, however their sizes will be limited by the distance between surface steps, as the growth direction rotates by 90° from terrace to terrace.…”
Section: Catalyst‐free Direct Cvd Growth Of Graphene On Technologicalmentioning
confidence: 99%
“…The researchers likewise established that the manufactured graphene flakes might be transported to additional substrates. To satisfy the unusual requirements, non‐metal constituents such as Si,, SiO 2, , and BN, were also used as substrates. However, non‐metal substrates exhibited disadvantageous restrictions together with deliberate evolution proportion and intermittent dimensions.…”
Section: Amalgamation Of Graphenementioning
confidence: 99%
“…The graphene films obtained by CVD methods displayed high flexibility, transparency and electrical conductivity [12,13], which is attractive for various electronic devices. Commonly, transition metals, such as Ge [14,15], Ni [16,17], Cu [18,19], Rh [20][21][22] and Co [23,24], are used as the substrates for the CVD growth of graphene films. Due to very low carbon solubility in Cu, ease of etching and feasibility of high-quality graphene transfer, Cu has emerged as a favoured substrate chosen mostly for the growth of large-area graphene films [25], which was first introduced by Ruoff's research group in 2009 [13].…”
Section: Chemical Vapour Depositionmentioning
confidence: 99%
“…They also demonstrated that as-synthesized graphene films could be transferred to other substrates (Figure 1b and c). To meet some special requirements, non-metal materials, such as Si [14,15], SiO 2 [26][27][28], BN [29,30] and Si 3 N 4 [31,32], were also used as substrates. However, the non-metal substrates showed the drawback limitations including slow growth rate and discontinuous size.…”
Section: Chemical Vapour Depositionmentioning
confidence: 99%